Factors Of Time Constraints For Memorizing The Quran And Learning Arabic In Higher Education - Zulkifli, Abdul Salam; Hj. Rofie, Mohamad Khadafi Bin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The tahfiz program in universities is one of the initiatives that help students sustain their Quranic memorization. Alternatively, the program's establishment aims to preserve the consistency of Quranic memorization amongst students currently pursuing professional studies at the tertiary level. Therefore, this research aims to analyze the contributing factors to time constraints that prevent effective outcomes of this particular program. This study is qualitative and depends much on in-depth interviews and document analysis techniques. The results of the study show that there are a relative number of challenges encountered by students that require consideration by all relevant parties, including academic workload, time restrictions, and the extracurricular activities organized by the faculties and colleges. This suggests that remarkable attention is necessary from appropriate parties to ensure the program's effectiveness and produce professional huffaz in the future. Insufficient focus on time management by the proper parties may adversely affect students' ability to implement the technique proposed by Muslim scholars for comprehending the verses of the Qur'an, which involves attaining proficiency in the Arabic language and its associated fields of knowledge.